Aspects of Financial Analysis Influencing the Quality of Business Valuation - Galinienė, Birutė; Mašalaitytė, Laura (Ekonomika, 2007)
This article presents an examination of the importance and influence of an analysis of a company’s financial condition on business valuation results. The accuracy and quality of a business valuation are directly related to the accuracy and reliability of the information presented. Business valuation practice in Lithuania has shoved. that without reliable internal information a business valuation is impossible, while without external information. a business valuation is inaccurate. A financial condition analysis of the company under valuation includes an valuation of its past, current and expected financial results. Business va1uers must gather comprehensive information and proceed with its analysis. However, not all of Lithuania’s business valuers react positively when given these requirements, and are often content to limit themselves to less comprehensive information on the object under valuation, not bothering to assess the surrounding circumstances. This article presents two aspects of the importance of and problems associated with a financial analysis - the investment aspect and the financial apsect. Literature that highlights the investment aspect often places a higher priority on the application of analytical methods, while the issue of the suitablity of information regarding financial responsibility is described merely as a difference in the existing record-keeping rules, and the problems arising from their comparison. In addition to the already mentioned detailed analysis problems, advocates of the financial aspect have identified many more and underline the necessity of closely assessing and distinguishing the results of the business under valuation for the actual business activities that are undertaken. The stages, actions and aims of a financial analysis encompass several stages, from identifying the record-keeping policies in use, through to the most important business evaluation results, as well as identifying potential areas for misrepresentation and their subsequent correction. It is in fact the very identification of misrepresentation and its correction that determines the reliability of data used in the business valuation, as well as the accuracy of the business valuation results. Taking into consideration the regulatory standards applied to business valuation and methodological recommendations, four main financial indicator groups in business valuation practice can be distinguished: profitability indicators; business effectiveness (asset management) indicators; solvency (liquidity) indicators; and capital structure indicators. A financial analysis can be based on both. smaller and a wider range of indicators, each reflecting the various aspects of the business concerned. Business valuers use their analytical systems. giving priority to those indicators they deem to be most important.